Die wissenschaftliche Internationale der Altertumskunde: Ein Brief Michael I. Rostovtzeﬀs an Alfred von Domaszewski - Rebenich, Stefan (Hyperboreus, 2021)
The article publishes a hitherto unknown letter from Michael I. Rostovtzeﬀ to the German ancient historian Alfred von Domaszewski which was written in the autumn of 1909. Rostovtzeﬀ discussed in nearly perfect German a Roman bronze object with a Latin inscription which might have been produced on the occasion of a military campaign. Its exact use was a controversial issue. The artifact was part of the extensive collection of the Russian Egyptologist Goleniščev. The letter illustrates Rostovtzeﬀ’s intense cooperation with German classicists. With German Altertumswissenschaftler he shared a strong commitment to the historical-critical method and to editorial enterprises. But Rostovtzeﬀ was able to combine diﬀerent sources and to integrate single testimonies into larger contexts. Small-scale research did not impede him from asking more far-reaching questions. He therefore tried to relate the bronze object to the political and military history of the Roman Empire. Through his academic cooperation, the Russian historian could integrate himself successfully into the international community of classical scholarship.